Risk Assessment to Dust Exposure in Room Maintenance: Analytical Study on Room Maintenance at PT. X (Persero) Building in Surabaya - Saiku Rokhim (State Islamic University of Sunan Ampel, 2017)
As one of the particulate chemicals, dust could occur in most of the production process and can create interference for workers health and safety. As one of the air pollution sources, dust could became a potential hazard which exist in room maintenances. Protection to workers is a must in order to reduce the risk of respiratory tract syndrome that often could be found in this cases. The aim of this study is to conduct a risk assessment to dust exposure in room maintenance, which held by contractors in PT. X (Persero) building in Surabaya. This is an cross sectional study with obsevation approach. The object of this research is the repairing works. The results indicate that the activities which could produce dust, such as: walls sanding using sandpaper, the tiles dismantle, sawmilling, the wood fiber refining, grinding, mixing and stirring cast materials, and room cleaning. Dust produced from a variety of works including sanddust, cement, lime, wood and dust mixed with paint. The results show that three types of works considere as high-risk activity (value > 12-25), 3 types of work consider as midle risk activities (value > 5-12), and one activity considered as a low-risk work (grades 1-5). The dusk factors controlling should be held regularly, in order to minimize the risk leveln againts the workers.